2003
DOI: 10.2307/3588399
|View full text |Cite
|
Sign up to set email alerts
|

A Corpus Analysis of Would-Clauses without Adjacent If-Clauses

Abstract: This article reports the findings of a corpus analysis of a grammatical structure taught in intermediate‐ or advanced‐level ESL/EFL texts: clauses that contain the modal would to signify hypothetical and counterfactual meaning. Contrary to the way these structures are represented in ESL/EFL textbooks—as would‐clauses adjacent to conditional clauses with if—these corpus data indicate that would‐clauses in counterfactual/hypothetical environments occur more often quite distant from or entirely without any corres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
16
0

Year Published

2004
2004
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(17 citation statements)
references
References 12 publications
(8 reference statements)
0
16
0
Order By: Relevance
“…Several researchers have compared grammar descriptions that are presented in textbooks with real world language use (Al-Wossabi, 2014;Barbieri and Eckhardt, 2007;Biber and Reppen, 2002;Carter, 1998;Eckhardt, 2001;Frazier, 2003;Gilmore, 2004;Khojasteh &Shakrpour, 2014;Šegedin, 2008) and, all have noted that there is a large gap between the explanations and descriptions in textbooks and real world language use. They attribute this to several factors: 1) textbook material is not taken from empirical data about language use but rely on writer's intuition; 2) textbooks present grammatical constructions as equally generalizable and of equal communicative importance; 3) information concerning pragmatics, discourse context and register is ignored; 4) textbooks are based on written norms; 5) textbooks simplify the grammar for pedagogical purposes (Barbieri and Eckhardt, 2007;Biber and Reppen, 2002;Carter and McCarthy, 1995;Lawson, 2001).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Several researchers have compared grammar descriptions that are presented in textbooks with real world language use (Al-Wossabi, 2014;Barbieri and Eckhardt, 2007;Biber and Reppen, 2002;Carter, 1998;Eckhardt, 2001;Frazier, 2003;Gilmore, 2004;Khojasteh &Shakrpour, 2014;Šegedin, 2008) and, all have noted that there is a large gap between the explanations and descriptions in textbooks and real world language use. They attribute this to several factors: 1) textbook material is not taken from empirical data about language use but rely on writer's intuition; 2) textbooks present grammatical constructions as equally generalizable and of equal communicative importance; 3) information concerning pragmatics, discourse context and register is ignored; 4) textbooks are based on written norms; 5) textbooks simplify the grammar for pedagogical purposes (Barbieri and Eckhardt, 2007;Biber and Reppen, 2002;Carter and McCarthy, 1995;Lawson, 2001).…”
Section: Methodsmentioning
confidence: 99%
“…There has been a lot of interest in Corpus Linguistics (CL) and its applications for second language acquisition (SLA) in recent years, and many studies have recommended using corpus-based findings to provide accurate content for prescriptive English grammar textbooks (Biber & Reppen, 2002;Conrad,1999;Carter & McCarthy, 1995;Frazier, 2003;Harwood, 2005;Kennedy, 2002;Lawson, 2001, Romer, 2010. Once thought of as only the domain of those interested in purely linguistic investigation, it is now seen as a useful tool for language teachers and SLA researchers for examining exactly how the language works in the real world.…”
mentioning
confidence: 99%
“…Many researchers have recommended the use of corpus-based findings to inform material writers as to L2 teaching materials (e.g. Biber & Reppen, 2002;Conrad, 1999;Carter & McCarthy, 1995;Frazier, 2003;Holmes, 1988;Harwood, 2005;Lawson, 2001, Romer, 2010, Kennedy, 2002. It is with the help of corpusbased studies that the "scope" of certain features can be investigated (Hulstijn, 1995), and according to Barbieri and Eckhardt (2007), "corpus-based analysis is an ideal tool to re-evaluate the order of presentation of linguistic features in textbooks and to make principled decisions about what to prioritize in textbook presentations".…”
Section: Introductionmentioning
confidence: 99%
“…Carter and McCarthy (), for example, note the frequency of ellipsis ([ I will ] see you next week ) and of left and right dislocation ( This one I haven't seen; He's a good guy, John is ) in spoken English. Scholars have called for greater attention to be paid to spoken grammar in English language teaching (Cullen & Kuo, ; Frazier, ; Jones & Waller, ), arguing that learners must be equipped with a full range of linguistic resources to communicate in a variety of situations (Carter & McCarthy, ; Mumford, ; Timmis, ). Cutting () has observed that vague language in spoken English, such as that kind of stuff , can serve as a marker of membership in a given speech community, and argues that this use can help learners show solidarity with first language (L1)–speaking peers.…”
mentioning
confidence: 99%